Konsep Khutbah Nikah dalam Khitbah dan Etika Kehidupan Pra-Nikah: Analisis Istinbāṭ Hukum dalam Kitab Fathul Mu’in - Pratama, Indra; Amar Adly, Muhammad (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
There are several forms of da’wah activities, including the sermon, which is a call or invitation to repentance, or an effort to change a situation to a better and more perfect one, both for individuals and for society. The khitbah is the initial step before marriage, aimed at increasing intimacy and peace of mind for the prospective couple in choosing their partner (husband/wife). During the khitbah, we are also permitted to cancel the khitbah. The sermon before this khitbah is sunnah to be delivered by each of the two bride and groom. The sermon before the khitbah can also be delegated, but to those appointed and agreed upon by each of the bride and groom, be it the groom or the bride. The khitbah, or proposal of marriage, is an important step in the Islamic marriage process, which has a legal and ethical basis regulated in the Qur’an, Hadith, and the views of scholars. This study aims to examine in depth the concept of khitbah, including its definition, requirements, and the limitations of seeing the genitals. Khitbah, or proposing marriage, is an important step in the Islamic marriage process which has a legal and ethical basis regulated in the Al-Qur’an, hadith and the views of ulama.